Kampanye Digital di Marketplace: Studi Resepsi Followers Akun Tokopedia di Instagram - Hamidah, Riqqah; Saragih, Nurhayani (Magister of Communication Science, Sahid University Jakarta., 2025)
This study aims to examine audience reception of the